Bilateral Simultaneous Heterotopic Ossification of the Reflected Head of Rectus Femoris Muscle: A Case Report and Review of the Literature - Murat Tonbul; Seyma Ozen; Ayse Tuba Tonbul (Case Reports in Orthopedics)
Lamellar bone formation in an abnormal location is defined as heterotopic ossification. It commonly occurs around the hip joint and most often involves the abductor muscles. It is a benign condition; however, its etiology remains largely unknown. Most previously reported cases have been due to trauma or intramuscular hemorrhage. In this paper, we present a case of bilateral heterotopic ossification of the reflected head of rectus femoris muscle without antecedent trauma or any other known cause, as the first and unique case in the literature. She was treated by excision of the right symptomatic bony mass via a modified Smith-Petersen approach. Postoperatively, she received 75 mg indomethacin daily for six weeks. She was pain-free and obtained full range of motion 3 weeks after the first intervention.